Two new species and one new country record of Protaphorura Absolon, 1901 (Collembola: Onychiuridae) from northeast China - Sun, Xin; Zhang, Bing; Wu, Donghui (Zootaxa, 2013)
One species new to China, Protaphorura bicampata (Gisin, 1956), and two new species, Protaphorura changbaiensis sp. nov. and Protaphorur minima sp. nov., are reported from northeast China. P. changbaiensis sp. nov. is similar to P. ajudagi and P. microcellata, but it can be distinguished from them by absence of a-pso on Th. II tergum. Protaphorura minima sp. nov. is chracterized by its male ventral organ on Abd. VI sternum. It can be separated from other species of the genus with the male ventral organ by the position of the male ventral organ and the dorsal pso formula.